2014
DOI: 10.1177/1524838014537907
|View full text |Cite
|
Sign up to set email alerts
|

Intercollegiate Athletes and Sexual Violence

Abstract: The 1990s saw the development of research on violence against women perpetrated by intercollegiate student-athletes. Research in this field stagnated during the last 15 years, despite the fact that this time period has evidenced multiple high-profile, even fatal, cases of violence against women at the hands of male student-athletes. These events prompted the Office of Civil Rights to call upon universities to more appropriately investigate and sanction perpetrators of sexual assault. The ensuing actions by uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 21 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…Researchers suggest that male-dominated environments such as those mentioned above are particularly likely to promote sexist attitudes and behaviors and may facilitate greater risk of sexual assault as well as victim-blaming myths (Sanday, 1990; Melnick, 1992; Koss and Gaines, 1993; Boeringer, 1996, 1999; Boswell and Spade, 1996; Bleecker and Murnen, 2005; McCray, 2014). Rape cultures are typically defined as hypermasculinized environments that glorify coercive sexual behavior as central to their group identity (O’Toole, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggest that male-dominated environments such as those mentioned above are particularly likely to promote sexist attitudes and behaviors and may facilitate greater risk of sexual assault as well as victim-blaming myths (Sanday, 1990; Melnick, 1992; Koss and Gaines, 1993; Boeringer, 1996, 1999; Boswell and Spade, 1996; Bleecker and Murnen, 2005; McCray, 2014). Rape cultures are typically defined as hypermasculinized environments that glorify coercive sexual behavior as central to their group identity (O’Toole, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Male intercollegiate athletes are at particularly high risk for perpetrating sexual violence (McCray, 2015). Intercollegiate athletes are athletes that represent their college or university in athletic events that are coordinated by an authoritative body (e.g., National Collegiate Athletic Association [NCAA]), against other colleges or universities.…”
mentioning
confidence: 99%
“…IHE have begun targeting student-athletes as the source of campus violence, primarily surrounding sexual assaults. There have been studies that suggest a connection exists between athletic participation and committing acts of sexual violence (Boeringer, 1996(Boeringer, , 1999Forbes et al, 2006;Frintner & Rubinson, 1993;Koss & Gaines, 1993;McCray, 2015;McMahon, 2011;Murnen & Kohlman, 2007;Young et al, 2017). Both research and media reports of sexually violent crimes Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Research attempting to correlate athletic participation with the propensity to be sexually violent is both vast and inconsistent. Many studies suggest a connection exists between athletic participation and sexual violence (Boeringer, 1996(Boeringer, , 1999Forbes et al, 2006;Frintner & Rubinson, 1993;Koss & Gaines, 1993;McCray, 2015;McMahon, 2011;Murnen & Kohlman, 2007;Young et al, 2017) while another body of scholarship has found no such connection exists (Caron et al, 1997;Crosset, Benedict, & McDonald, 1995;Gidycz, Warkentin, & Orchowski, 2007;Smith & Stewart, 2003). Moreover, researchers have questioned the findings and assertions between athletic participation and sexual violence due to methodological concerns (Crosset, 1999;Kimble, Russo, Bergman, & Galindo, 2010;Koss & Gaines, 1993).…”
Section: Sexual Violence and Intercollegiate Student-athletesmentioning
confidence: 99%
See 1 more Smart Citation